2020
DOI: 10.1021/acs.est.0c06052
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-Induced Epigenetic Toxicity in Zebrafish: Experimental and Molecular Dynamics Simulation Studies

Abstract: The increased detection of many prescription drugs in aquatic environments has heightened concerns of their potential ecotoxicological effects. In this study, the effects of metformin (MEF) exposure on tissue accumulation, gene expression, and global DNA methylation (GDM) in zebrafish were investigated. The toxic mechanism of MEF exposure was simulated by molecular dynamics (MD) to reveal any conformational changes to DNA methyltransferase 1 (DNMT1). The results showed MEF accumulation in the gills, gut, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Low-dose metformin exposure for a long time could cause a significant upregulation of numerous endocrine-related genes in FHM [ 28 ]. Metformin affected the expression of genes related to neurological and cardiovascular development and the expression of CYP3A65, GSTM1, p53, and DNMT1 genes in the liver in zebrafish [ 29 , 30 ]. It was also found that metformin could induce oxidative stress and the two-generation endocrine disruption in Oryzias latipes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose metformin exposure for a long time could cause a significant upregulation of numerous endocrine-related genes in FHM [ 28 ]. Metformin affected the expression of genes related to neurological and cardiovascular development and the expression of CYP3A65, GSTM1, p53, and DNMT1 genes in the liver in zebrafish [ 29 , 30 ]. It was also found that metformin could induce oxidative stress and the two-generation endocrine disruption in Oryzias latipes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“… 78 Furthermore, it was found to accumulate in the liver, causing toxicity after prolonged aquatic exposure in adult zebrafish. 79 …”
Section: Resultsmentioning
confidence: 99%
“…Many studies , have demonstrated the success of the MM/PBSA method for estimating the binding free energies of small molecules to macromolecules. Before calculating the binding free energies, we first analyzed the dynamic stability of the two IL/AChE complexes through an RMSD (root-mean-square deviation) analysis.…”
Section: Results and Discussionmentioning
confidence: 99%